2018
DOI: 10.4467/25438700sm.18.070.9660
|View full text |Cite
|
Sign up to set email alerts
|

Współczesne miasta Zagłębia Ruhry – zielone poprzemysłowe aglomeracje

Abstract: StreszczenieZagłębie Ruhry przez dziesięciolecia było najbardziej zanieczyszczonym obszarem Niemiec. Pod koniec lat 80. XX wieku, kiedy zakończono produkcję w zakładach przemysłowych i zamknięto kopalnie rozpoczął się proces rewitalizacji w ramach IBA Emscher Park, który trwał do 1999r. Obecnie po prawie 20 latach po zakończeniu IBA można obserwować wieloletnie efekty działania całego procesu transformacji. Połączenie dziedzictwa kulturowego dawnych terenów przemysłowych naturalnym krajobrazem i nadanie im zup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There is also a number of voices calling for preserving post-industrial facilities and indicating their new functions. Currently, after a number of years, it might be observed that the Ruhry District has become one of the most popular touristic attractions in Germany' (Kusińska, 2018).…”
Section: Local Communitys' Attitudes Towards Post-industrial Heritagementioning
confidence: 99%
See 1 more Smart Citation
“…There is also a number of voices calling for preserving post-industrial facilities and indicating their new functions. Currently, after a number of years, it might be observed that the Ruhry District has become one of the most popular touristic attractions in Germany' (Kusińska, 2018).…”
Section: Local Communitys' Attitudes Towards Post-industrial Heritagementioning
confidence: 99%
“…The survey was carried out in February 2019 and documents the situation on 28 th February 2019 8. References: information entitled 'Facebook for 10 years in Poland.…”
mentioning
confidence: 99%